An Introduction to Voice Search - Wang, Ye-Yi; Yu, Dong; Ju, Yun-Cheng; Acero, Alex; Ju, Y. C. (IEEE Signal Processing Magazine (Special Issue on Spoken Language Technology), 2008)
A look at the technology, the technological challenges, and the solutions.